Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Konsumen Motor Honda di Jakarta Timur - Irdham Hawari; Purwatiningsih Purwatiningsih; Ratih Setyo Rini (STIKes Ibnu Sina Ajibarang, 2024)
This research in marketing management aims to determine the effect of product quality and price on consumer satisfaction for East Jakarta Honda motorbikes from April to June due to the decline in sales of Hodna motorbikes on consumer satisfaction in 2022. The aim of this research is to determine product quality and price on Honda motorbike consumer satisfaction in East Jakarta and to study marketing management techniques. This type of research is quantitative research, the sampling technique is Cluster Sampling which was obtained by 60 respondents which was carried out in the East Jakarta District, totaling 10 sub-districts. The data collection method used was distributing questionnaires. In this research, the SPSS version 25 program was used. The results of the research on the influence of product quality and price on customer satisfaction for Honda motorbikes showed results that had a very positive influence on partial and simultaneous results. Which means increasing product quality and product prices. So the results are very significant, the T test is 0.044 > 0.5 and the F test is 1.041 > F is 2.00, the more satisfaction Honda motorbike customers increase, the more sales they make to customers.